Effect of different friction coefficient models on numerical simulation of inertia friction welding of 2219 Al alloy to 304 stainless steel - Hao Wang; Guoliang Qin; Changan Li (Journal of Materials Research and Technology, 2023)
In inertia friction welding (IFW) of Al alloy to steel, the friction coefficient of interface influences the friction heat production and determines the accuracy of the numerical simulation of welding process. A fully coupled three-dimensional model was established to simulate the IFW process of 2219 Al alloy to 304 stainless steel. By taking different simplifications in the influencing factors (i.e., temperature, sliding velocity, and pressure) of friction coefficient, three types of friction coefficient models were established and utilized in the simulation of IFW process. The strain compensated Arrhenius and Johnson-Cook models were employed to describe the deformation behavior of Al alloy and steel, respectively. Both Al alloy and steel were assumed to be the elastic-plastic body, and the friction stress was calculated by the Coulomb friction model. The friction interface temperature, angular velocity attenuation, axial shortening distance, and joint appearance were measured to verify and compare the accuracy of the established models. The temperature and stress evolutions during the IFW process were also analyzed. With the smallest error in validation, the friction coefficient model, which was a function of temperature, sliding rate, and pressure, showed the best accuracy in describing the friction behavior. By considering the effect of pressure, a more accurate shear stress at the center region of the interface was calculated with a lower value. It means that the friction resistance at the region was lower, promoting the flow of internal Al alloy and the formation of curly-shape flash.